ANALYSIS OF THE KHON DANCE AND SONGKRAN FESTIVAL CONFLICT BETWEEN THAILAND AND CAMBODIA ON THE REGISTRATION OF INTANGIBLE CULTURAL HERITAGE AT UNESCO: ANALISIS KONFLIK TARI KHON DAN FESTIVAL SONGKRAN ANTARA THAILAND DAN KAMBOJA PADA PENDAFTARAN WARISAN BUDAYA TAKBENDA DI UNESCO - Akbar Bagaskara; Aldia Wulandari; Uswatun Khasanah; Muhammad Andika Azmi; Putri Dwiaggini (GETER : Jurnal Seni Drama, Tari dan Musik, 2026)
his article aims to examine the cultural conflict and diplomacy that occurred between Thailand and Cambodia regarding the designation of the Khon dance and the Songkran festival as UNESCO Intangible Cultural Heritage. Although several studies have discussed cultural heritage disputes in Southeast Asia, there is still limited research specifically examining how UNESCO recognition strengthens cultural nationalism between Thailand and Cambodia. This study aims to analyze how this recognition shapes national identity, political narratives, and bilateral relations between the two countries. This study uses a qualitative approach through document analysis and media discourse analysis using triangulation techniques. Data are drawn and collected from official UNESCO documents, government statements, and media coverage in both countries to understand the historical context and contemporary dynamics that have occurred. The findings indicate that UNESCO recognition can strengthen nationalist narratives and also trigger digital conflicts through the media and public sphere. However, on the other hand, this recognition also opens opportunities for cultural diplomacy and regional cooperation. Claims to cultural heritage are strategically mobilized by state and non-state actors to strengthen national identity and cultural legitimacy. This study emphasizes that intangible cultural heritage plays a dual role as a source of conflict and a means of cooperation, thus requiring a collaborative and inclusive approach in its management in the Southeast Asian region.